(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To analyze the prevalence of stunting and associated factors among children in Phieng Luong commune, Bac Me district, Ha Giang province. Subjects and methods: A cross-sectional descriptive study was conducted among 214 children under five years of age in Phieng Luong commune, Bac Me district, Ha Giang province. Results: The mean age of the children was 27.8 ± 16.3 months. The prevalence of stunting was 65.4%, of which 28.0% were classified as severe stunting. Children whose mothers were shorter than 150 cm, had an educational level below high school, belonged to families with three or more children, or whose mothers had inadequate knowledge of child feeding and care had significantly higher rates of stunting than their counterparts (p < 0.05). Multivariable analysis identified maternal height below 150 cm as an independent factor associated with stunting. Conclusion: The prevalence of stunting among children in the study area remains alarmingly high. Maternal height below 150 cm was identified as an independent factor associated with stunting. Maternal education level and knowledge of child feeding and care play important roles in improving children’s nutritional status